Effects of high altitude on substrate use and metabolic economy: Cause and effect? - Braun, B. (Medicine & Science in Sports & Exercise, 2008)
In a variety of experimental models, hypoxia causes a shift in substrate use to favor increased dependence on glucose. One explanation for this phenomenon is a selective advantage derived from the increased metabolic economy (more ATP derived per unit oxygen consumed) that results when glucose is oxidized rather than lipid. In support of this hypothesis, after acclimatization to hypoxia, lower oxygen consumption at a given submaximal workload has often been reported. However, evidence from several experimental models is inconsistent with the idea that the increase in glucose use is causally related to greater metabolic economy.